Educational reality in Comenius’ views – the content aspect of comeniology - Florczykiewicz, Janina (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
The text proposes an approach to comeniology in the subjective perspective focusing on the content dimension of the research process. The considerations were based on the approach to science presented in Polish literature as a system of theorems about reality developed in the course of research. Comenius’ work is considered from the perspective of the description of educational reality contained in it, which is composed of his concept of education. The intention was to present truths about the world, man and relations between them, objectively recognized by the author. The views on the concept of man, teacher and upbringing were reconstructed. A description of the educational reality outlined by the author was presented, taking into account the three elements constituting it - the concept of man, upbringing and teacher. The intention was only to mention the most relevant content, because an exhaustive discussion goes beyond the scope of the article.